BENTUK DAN PENGGUNAAN KATA PENGGOLONG BENDA DI PASAR INDUK TRADISIONAL DI JAKARTA DAN SURABAYA - Nadra, Nadra; Wahyuni, Sri; Mahsun, Mahsun (LITERA, 2014)
This study aims to describe forms of noun classifiers and their uses by Indonesian speakers in transactions in traditional central markets in Jakarta and Surabaya. The data were collected through listening and interviewing. They were analyzed by the intralingual correspondence technique. The research findings are as follows. First, there are 43 forms of noun classifiers. Second, they can be classified into three categories, i.e.: (a) individual noun classifiers, (b) collective noun classifiers, and (c) noun classifiers in the form of measurement units. Third, the dominant noun classifiers in traditional central markets in Jakarta and Surabaya are noun classifiers in the form of measurement units. This is due to the fact that transactions need precise measurements.